2014
DOI: 10.1177/1074248413518968
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Alternate Day Therapy With Atorvastatin and Fenofibrate Combination in Mixed Dyslipidemia

Abstract: Alternate day therapy with atorvastatin-fenofibrate combination is an effective and safe alternative to daily therapy in mixed dyslipidemia. Apart from significant cost savings, reasonable reduction in the incidence of adverse events is seen with alternate day regimen. However, larger studies are needed to more reliably confirm our interesting but preliminary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…20) Treatment with atorvastatin, in particular, has been shown to be superior in preventing and treating cardiovascular disease. [21][22][23] Correlation analysis suggested that Tregs frequency and function positively are correlated with left ventricular ejection fraction, but negatively correlated with left ventricular end-diastolic dimension and Nterminal pro-brain natriuretic peptide (NT-proBNP) in patients with CHF. 24) Zhang, et al 25) demonstrated that atorvastatin treatment was associated with reduced all-cause mortality and readmission rate for heart failure (HF), and the superiority of statin therapy was significant in CHF patients younger than 65 years.…”
mentioning
confidence: 99%
“…20) Treatment with atorvastatin, in particular, has been shown to be superior in preventing and treating cardiovascular disease. [21][22][23] Correlation analysis suggested that Tregs frequency and function positively are correlated with left ventricular ejection fraction, but negatively correlated with left ventricular end-diastolic dimension and Nterminal pro-brain natriuretic peptide (NT-proBNP) in patients with CHF. 24) Zhang, et al 25) demonstrated that atorvastatin treatment was associated with reduced all-cause mortality and readmission rate for heart failure (HF), and the superiority of statin therapy was significant in CHF patients younger than 65 years.…”
mentioning
confidence: 99%
“…The level of serum HDL-c was elevated by XKA (1.5 g/kg) by 24.5 %. TC-HDL-c ratio is an independent predictors of coronary heart disease (CHD) events [ 22 ]. In XKA (1.5 g/kg and 0.75 g/kg) treatment groups, TC-HDL-c ratio of KKAy mice was significantly lowered by 12.0 % and 9.2 %, respectively.…”
Section: Resultsmentioning
confidence: 99%